PAULO FREIRE - THE ANNOUNCEMENT OF HOPE - Andreatta Whitaker, Dulce Consuelo [UNESP]; Vitorino, Diego da Costa; Fiamengue, Elis Cristina (Centro Univ Nove Julho, 2021)
In this article, we discuss the intellectual work of the Brazilian patron of education. The peculiar look towards this great and multifaceted author has helped us to understand him better. What is more, his hopeful side has also contributed to a better understanding of his thoughts. This points to an encouragement and counterpoint form against the advance of neoconservative wave in Brazil. In this way, we have analyzed Paulo Freire by some perspectives such: women influence in his life, his thinking reflections, and the social contexts that helped him elaborate his scientific practice. Besides, he has been studied by the persecution bias, conservatism, and authoritarianism in Brazilian society, from the past to nowadays. Despite the advance of the ultraconservative wave, we have learned from our patron that education must not be seen as a reproductive process but as a liberating one. In this sense, it should be faced as an important social technology to promote autonomy, not oppression, and to encourage humanizing and liberating forms of social action. Freire' s work is a foreshadowing of hope.
Keywords: liberating education; reproductive education; hope; neoconservatism; Freire's intellectual trajectory